Proyecto de factibilidad para la creación de una empresa productora y comercializadora de chocolate en barra en el cantón el Pangui de la provincia de Zamora Chinchipe para el año 2015 - Saetama Fajardo, Johana Susana (2017)
The present project of feasibility was developed in the canton Pangui, county of Zamora Chinchipe, being its main objective to implement a company producer and comercializadora of chocolate in bar for the canton Pangui. With this objective the analysis was made based on the such methods as the inductive, deductive and statistical, besides the investigation techniques like the direct observation, he/she interviews and the survey that was applied 355 people according to the calculation of the sample. Before the methodology and the described techniques he/she was carried out the calculation of results; In the market study a potential demand of 4.548, was determined a real demand of 2.547, and an effective demand in units of 2.471 bars of chocolate, an offer of 1.494 of that which an unsatisfied demand of 138.893 is obtained With the Technical study it was determined, the size considering the conditioning factors for an appropriate infrastructure like they are the demand, the readiness of inputs, the physical space that allows to carry out the production processes, in engineering of the project showed up the productive process in all its phases and commercialization of the product finished with an installed capacity of the plant of 104.000 units with which we cover 75% of the market in the first year of the project In the Organizational Study, it was determined the legal constitution of the company like Limited Company, this with previous consideration that he/she lends this type of companies. In this company it was also determined the respective flowcharts like structural, functional and the posicional and in that way a manual of functions was structured for all the positions to carry out in the company with its minimum requirements. The Financial Study shows the initial investment of the project a total of $74.028,89 and its possible financing they noticed a social capital of $68948.07 dollars and the difference with a bank credit of $5.080,82 dollars. With the Financial Evaluation you could determine that the Current Net Value of the present project is favorable, what means that the value of the company will have an increment of $95.403.60 and it is for that reason that the project is accepted. The capital recovery is calculated that he/she will be carried out it 2 years in 3 months 10 days inferior time to the lifespan of the project. While The Internal Rate of Return of the present project is of 37,22% for what is determined that the project according to the evaluation approaches the project is feasible its realization. According to the determination of the relationship I benefit cost it is determined that for each invested dollar we obtain hundredth $0,60 of gain. Later on, the company supports until an increment in its costs of until 35% and a decrease of its revenues until 15%. The Environmental impact that presents this project of feasibility won't be of more incidence or affectation since is a product elaborated without chemical and the wastes of the same one will have a treatment that you/they don't provoke taponamiento of the sewers. In the social part this he/she has a significant impact for what takes advantage the local inputs and it generates bigger work sources. In the conclusions it was ratified that the project is profitable since high revenues will be obtained and it will contribute in the impulse of the development in Zamora's county Chinchipe because the economy will reach a bigger dynamism for the flow of money that will provoke the implementation of this business.